Increased risk for ischaemic events is related to combined RAS polymorphism. Issue 4 (1st April 2001) - van Geel, P P; Pinto, Y M; Zwinderman, A H; Henning, R H; van Boven, A J; Jukema, J W; Bruschke, A V G; Kastelein, J J P; van Gilst, W H
Abstract : OBJECTIVE: To determine whether the angiotensin converting enzyme (ACE) and the angiotensin II type 1 receptor (AT1 R A1166C) gene polymorphism interact to increase the risk of ischaemic events, and whether this can be explained by the progression of angiographically defined coronary atherosclerosis. DESIGN: Prospective defined substudy of the lipid lowering regression trial (REGRESS). SETTING: University hospital. PATIENTS: 885 male patients with stable coronary artery disease. MAIN OUTCOME MEASURES: Incidence of ischaemic events during a two year follow up; serial quantitative coronary arteriography (mean segment diameter and minimum obstruction diameter) at baseline and after two years. RESULTS: Patients who carried both the ACE-DD and AT1 R-CC genotype had significantly more ischaemic events during the two year follow up than those carrying other genotype combinations (p = 0.035, Mantel-Haenszel test for linear association). There was no association between the two genotypes and mean segment diameter or minimum obstruction diameter at baseline or after two years. CONCLUSIONS: The suggestion that ACE-DD and AT1 R-CC genotypes interact to increase the risk of ischaemic events is confirmed. However, this increased risk was not accompanied by increased progression of angiographically defined coronary atherosclerosis.